1977
DOI: 10.1901/jaba.1977.10-605
|View full text |Cite
|
Sign up to set email alerts
|

A PARENT ADVICE PACKAGE FOR FAMILY SHOPPING TRIPS: DEVELOPMENT AND EVALUATION1

Abstract: THIS ARTICLE REPORTS ON THE PRIMARY STEPS IN THE DEVELOPMENT OF PARENT ADVICE FOR POPULAR DISSEMINATION: (a) developing advice for one specific problem situation, family shopping trips; (b) testing the advice program for benefit to children and convenience to adults; and (c) packaging the advice so it can be used successfully by interested parents. Systematic observation of 12 families using the written advice package on shopping trips revealed its effectiveness in reducing child disruptions and increasing pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

1980
1980
2009
2009

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…At the same time, many parents report that shopping trips with their children are an exhausting and stressful experience, and that the supermarket is a setting in which disruptive behaviors are common [15]. Problem behaviors such as product disturbance, demanding and wandering around are common for both non-problem and behaviorally disturbed children [16,17]. An earlier study by Sanders and Hunter [18] sought the views of 100 parents on the nature of difficulties parents experience with children on trips to the supermarket.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, many parents report that shopping trips with their children are an exhausting and stressful experience, and that the supermarket is a setting in which disruptive behaviors are common [15]. Problem behaviors such as product disturbance, demanding and wandering around are common for both non-problem and behaviorally disturbed children [16,17]. An earlier study by Sanders and Hunter [18] sought the views of 100 parents on the nature of difficulties parents experience with children on trips to the supermarket.…”
Section: Introductionmentioning
confidence: 99%
“…Grocery stores are places where parent-child behavior deteriorates. It turns out that simple advice packages, distributed to parents, observably changed parent-child interactions for the better while shopping~e.g., Clark, Greene, Macrae, McNees, Davis, & Risley, 1977;Ergon-Rowe, Ichinose, & Clark, 1991!. In studies of preschoolers, my co-workers and I have been able to change parent-hild behavior while shopping using specially designed shopping bags, distributed in the store, that have sticker charts for the child.…”
Section: Embry 2002mentioning
confidence: 99%
“…First, social and educational comments of a noncollective nature (i.e., exclusively between parents or a parent and a child) occurred to a lesser degree during Table-Tradi- Table-No-ma-Tradi- Table-No-ma-Tradi- It is uncertain how these findings may be limited by reactive effects, which are potentially problematic in most studies of family interactions. As in previous studies (Bauman et al, 1983;Clark et al, 1977), families in this study were aware of being videotaped/observed. It is not dear whether any of them behaved differently than he or she ordinarily would have.…”
Section: Other Behaviorsmentioning
confidence: 99%
“…In a study illustrative of this approach, Clark, Greene, Macrae, McNees, Davis, and Risley (1977) We thank Jim Middleton, Jim Renshaw, and the numerous cooperative restaurant personnel; Lin Muldoon and her fine staff of the Child Development Lab; the helpful teachers, staff, and students of Carbondale New School; the Lutzker and Seibel families; artist Charlotte Easton; the families who participated in this study; and the graduate assistants who made it possible.…”
mentioning
confidence: 99%